Experiencia educativa de la asignatura Farmacognosia en el contexto de la pandemia (Experiencias) - Sülsen, Valeria (2021)
The Covid-19 pandemic has impacted on different educational levels, including university. In this sense, the contents of the classrooms (seminars and practical works) of Pharmacognosy, subject of the eighth semester of Pharmacy studies of the University of Buenos Aires, were adapted to the virtual instance. At the same time, various strategies and the implementation of tools were used to promote communication, active participation of students, understanding of the contents and collaborative work. The results obtained, referring to the implementation of platforms and resources on the issues of extractive processes and phytochemical groups I, are encouraging and demonstrate the interest and participation of the students contributing to the teaching-learning process in the virtual instance.